Oxygen Defect Engineering Promotes Synergy Between Adsorbate Evolution and Single Lattice Oxygen Mechanisms of OER in Transition Metal‐Based (oxy)Hydroxide - Yu‐Han Wang; Lei Li; Jinghui Shi; Meng‐Yuan Xie; Jianhang Nie; Gui‐Fang Huang; Bo Li; Wangyu Hu; Anlian Pan; Wei‐Qing Huang (Advanced Science, 2023)
Abstract The oxygen evolution reaction (OER) activity of transition metal (TM)‐based (oxy)hydroxide is dominated by the number and nature of surface active sites, which are generally considered to be TM atoms occupying less than half of surface sites, with most being inactive oxygen atoms. Herein, based on an in situ competing growth strategy of bimetallic ions and OH− ions, a facile one‐step method is proposed to modulate oxygen defects in NiFe‐layered double hydroxide (NiFe‐LDH)/FeOOH heterostructure, which may trigger the single lattice oxygen mechanism (sLOM). Interestingly, by only varying the addition of H2O2, one can simultaneously regulate the concentration of oxygen defects, the valence of metal sites, and the ratio of components. The proper oxygen defects promote synergy between the adsorbate evolution mechanism (AEM, metal redox chemistry) and sLOM (oxygen redox chemistry) of OER in NiFe‐based (oxy)hydroxide, practically maximizing the use of surface TM and oxygen atoms as active sites. Consequently, the optimal NiFe‐LDH/FeOOH heterostructure outperforms the reported non‐noble OER catalysts in electrocatalytic activity, with an overpotential of 177 mV to deliver a current density of 20 mA cm−2 and high stability. The novel strategy exemplifies a facile and versatile approach to designing highly active TM‐LDH‐based OER electrocatalysts for energy and environmental applications.